Experimental and computational assessment of disbond growth and fatigue life of bonded joints and patch repairs for primary airframe structures. (June 2022) - Tanulia, Veldyanto; Wang, John; Pearce, Garth M.; Baker, Alan; Chang, Paul; Gangadhara Prusty, B.
Highlights: Implementation of slow growth design strategy for bonded joints/patch repairs for primary aircraft structures, consistent with FAA guidance. Static and fatigue testing of a novel specimen configuration to identify the entire disbond crack growth process. Indication of slow growth management approach feasible for bonded joints/patch repairs if the doubler/patch is designed to be sufficiently long. Establishment of modified Paris law for predicting allowable fatigue life and determining inspection interval, in accordance with FAA guidance. Potential solution for maintenance cost reduction for primary aircraft structures. Abstract: The applicability of a damage slow growth management strategy to bonded joints/patch repairs of primary aircraft structures was evaluated through an experimental and computational study. Fatigue tests were conducted to investigate the entire process of disbond growth from initiation up to joint ultimate failure. The residual static strength of the joint as a function of disbond length was established using finite element modelling, in which the mesh size was calibrated using the static strength of the specimens measured in room temperature and dry (RD) and hot-wet (HW) conditions, based on the characteristic distance approach. A virtual crack close technique (VCCT) approach was utilised to assess the strain energy release rates (SERRs) as a function of disbond crack length. The measured disbond growth rates were correlated with the SERRs using a modified Paris law that enabled prediction of joint fatigue life. The fatigue test results indicated that for a joint having a sufficient static strength safety margin under a typical fatigue loading that would propagate disbond, the disbond growth would be stable in a particular length range. Thus, the slow growth approach would be feasible for a bonded joint/patch repairs if the patch is designed to be sufficiently large to allow extended damage propagation (whilst in the case when patch size must be limited, safe-life design for the patch termination region in critical repairs must be considered. Should disbond growth occur in this case, the joint must be repaired or replaced). The work presented in this paper validated the framework/procedure proposed previously by the authors (Tanulia et al., 2020) for managing damage slow growth in bonded joints/patch repairs. In the last part of this paper the planned follow-on research is briefly described.